Prevalence and Awareness of Hypertension among Adults and its Related Risk Factors - Maharjan, Basant (Journal of Nepal Health Research Council, 2018)
Background: Hypertension is a modifiable risk factor for cardiovascular diseases. Various studies conducted in the world showed high prevalence of hypertension, which is in increasing trend in Nepal also. The aim of this study was to assess hypertension status and risk behaviours among adult population in Kirtipur Municipality. Methods: A cross sectional descriptive study was conducted among 580 adults of age 20 - 59 from December 2015 to April 2016. Data was collected by observation method to determine hypertension prevalence and Body Mass Index. Questionnaire was used to assess exposure to the risk factors. Results: Among all hypertension prevalence was 37.0% (215 out of 580). The prevalence was 41.6% (110 out of 264) among male and 32.2% (105 out of 316) among female (P